2017
DOI: 10.1123/iscj.2017-0062
|View full text |Cite
|
Sign up to set email alerts
|

“Pleased To Be Sacked”: Coach Pat Lam’s ‘Learnings’ and the Evolution of a Professional Rugby Union Organisation

Abstract: In 2012 Pat Lam was dismissed (‘sacked’) as head coach of the Auckland Blues, a professional rugby union team in New Zealand. Within months of his sacking Lam had become the head coach of Connacht Rugby; an improving, but midlower table, professional provincial team in the west of Ireland. The purpose of this ‘best practice’ article is twofold. First, to illustrate how Lam used his dismissal (‘sacking’) from the Auckland Blues as a pivotal opportunity to learn, and develop, as a coach. Specifically his imperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…45 In addition to these findings articulating a clear vision to the players provides a starting point to design and implement team principles, game strategies and behaviours. This resonates with previous research conducted by Byrne and Cassidy 27 in which they suggested ‘a vision drives leadership and leadership drives performance’ (p. 328).…”
Section: Clarity Of Visionsupporting
confidence: 88%
See 1 more Smart Citation
“…45 In addition to these findings articulating a clear vision to the players provides a starting point to design and implement team principles, game strategies and behaviours. This resonates with previous research conducted by Byrne and Cassidy 27 in which they suggested ‘a vision drives leadership and leadership drives performance’ (p. 328).…”
Section: Clarity Of Visionsupporting
confidence: 88%
“…VBL has been researched in rugby union. 27 In this study they investigated a rugby union coach who applied an authentic coaching philosophy or 'belief triad' (leadership, culture, game strategy) which was underpinned by the coach's core values and behaviour within a different culture.…”
Section: Introductionmentioning
confidence: 99%